Bone lid technique versus standard technique for treatment of mandibular lesions - Mona S. Sheta; Rehab F. Ghouraba; Marwa T. Ibrahim (BMC, 2024)
Abstract Background Jaw lesions are frequent in the oral and maxillofacial areas. Different methods for enucleating jaw lesions in the oral and maxillofacial sites have been proposed, including the bone lid technique. Purpose The aim of this study was to compare the clinical and radiographic results of the bone lid technique employing a piezoelectric surgery to the traditional technique in individuals with mandibular lesions. Materials and methods A randomized controlled trial was conducted on 24 patients with mandibular lesions. They were randomly allocated into two groups (n = 12 for each group). Group I: the mandibular lesion was excised with bone lid technique using a piezoelectric device, followed by the fixation of the bony window after its repositioning. Group II: the lesion was excised with the traditional method using rotatory burs. Pain, soft tissue healing, bone exposure, bone lid integration, and the volume of the residual bone defect were all assessed clinically and radiographically after one week, one month, and six months. Results All patients in both groups showed adequate soft tissue healing except for one case in group I experienced wound dehiscence and bone lid exposure. The bone lid group reported significantly less pain than the usual approach at the 3rd and 7th days. After six months, the volume of bone defect filling was considerably higher in the bone lid group compared to the conventional group. Conclusion The bone lid technique was an effective procedure in the management of mandibular lesions compared to the standard method. Besides, this technique provides better bone healing and reduces bone loss. Trial registration This clinical trial was registered at clinicaltrials.gov on 14/8/2023 and had registration number NCT05987930.